Providing Education About Caesarean Sectio Operations To Pregnant Women Who Will Understand Caesarean Sectio Operations To Reduce Pre-Operative Anxiety - Solikhah, Fitriana Kurniasari; Arif, Taufan; Tyas, Maria Diah Ciptaning (Tarqabin Nusantara Group, 2024)
Sectio caesarea (SC) is a method of expelling a baby by performing surgery on the mother's abdominal wall and uterus. Apart from having painful side effects and a large risk of complications, a Caesarean section is also a major medical procedure that can cause fear, anxiety, worry and stress for pregnant women who will undergo it. Providing appropriate education to pregnant women who will undergo a cesarean section can help reduce anxiety levels before surgery. This community service activity is to increase pregnant women's knowledge about caesarean section operations. reduce the anxiety of pregnant women who will undergo caesarean section surgery. and prepare pregnant women physically and mentally to face caesarean section surgery. The number of participants in this community service activity was 20 pregnant women who were about to undergo a Caesarean section. Pregnant women understood about Caesarean section operations, benefits, risks and surgical procedures. The anxiety of pregnant women who will undergo caesarean section surgery has decreased. Pregnant women feel more physically and mentally prepared to face caesarean section surgery. Education about caesarean section surgery can increase knowledge and reduce anxiety of pregnant women who will undergo caesarean section surgery.